Competitiveness and Impact of Government Policies on the Development of People's Arabica Coffee Plantations Partnership Pattern in Solok Regency - Faidil Tanjung; Rafnel Azhari; Erwin Erwin (International Journal Labs, 2023)
This study aims to analyze the competitiveness of Arabica coffee commodities and analyze the impact of government policies on Arabica coffee commodities in Solok Regency. This research data analysis method uses the Policy Analysis Matrix (PAM). The results showed that the Arabica coffee plantation business in Solok Regency has competitiveness both in terms of competitive advantage and comparative advantage, where the value of the ratio of private costs and domestic cost ratios obtained is less than one, namely 0.48 and 0.41. For the impact of the Arabica coffee output policy, the private price of Arabica coffee is lower than the social price. The impact of the production input policy causes the private price of tradable input to be higher than the social price, and the impact of the input-output policy causes a decrease in the producer surplus, meaning that there is no economic incentive to increase Arabica coffee production. The suggestion from this research is expected that farmers can increase the productivity of Arabica coffee than the government is expected to expand the planting area and facilitate the provision of superior seeds. The government is also expected to stabilize the selling price of Arabica coffee at the farmer level.